The situation of the journalist and journalism in the modern media system - fakultetas, Komunikacijos (Žurnalistikos tyrimai, 2009)
Vilnius University, Small Hall, 2009 11 05In 2009, the Vilnius University Institute of Journalism held a scholarly conference marking 60 years of journalism education. The event gathered researchers and lecturers to reflect on the evolving identity of journalists, challenges of media ethics, the scientific development of journalism, and the growing political influence of the media. Presentations addressed the role of journalism in shaping public discourse, the ethical use of language, and media responsibility in democratic societies. Particular attention was given to the media’s political agency and its potential to initiate or influence social processes. The conference reinforced the importance of university education in journalism as a foundation for ethical thinking and critical public communication.
Keywords: Journalism; Ethics; Media and politics; Professional identity; Communication studies